Minat Pelaporan Pajak dengan E-filling: Kualitas Pelayanan, Manfaat Teknologi Informasi dan Kemudahan Pengguna - Dipateruna Awaloedin; Elwisam Elwisam (Oikonomia: Jurnal Manajemen, 2023)
Purpose In accordance with the technology acceptance model and theory of planned behavior, this study aims to examine the perceived benefits and convenience level of the e-filling system and the quality of KPP services that help people in e-filling with interest in tax reporting by e-filling. Methodology This research design is a cross-sectional design. The data collected is primary data of 100 samples from a population of 20,332 individual taxpayers at the Depok Sawangan tax office. Determination of the sample by convenience sampling technique and measured by the slovin formula. Single harman factor testing was also carried out. While testing the hypothesis with multiple regression through SPSS 26. Findings Quality of service and convenience perceived by taxpayers affects the interest of taxpayers in reporting their taxes by e-filling. Meanwhile, the benefits felt by taxpayers do not affect the interest in using e-filling. Suggestion Practical implications and suggestions for research are described in this article.